1999
DOI: 10.1104/pp.120.4.1049
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization and Expression Analysis of the Amino Acid Permease RcAAP3 from Castor Bean1

Abstract: A polymerase chain reaction-based library screening procedure was used to isolate RcAAP3, an amino acid permease cDNA from castor bean (Ricinus communis). RcAAP3 is 1.7 kb in length, with an open reading frame that encodes a protein with a calculated molecular mass of 51 kD. Hydropathy analysis indicates that the RcAAP3 protein is highly hydrophobic in nature with nine to 11 putative transmembrane domains. RcAAP3-mediated uptake of citrulline in a yeast transport mutant showed saturable kinetics with a K m of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
3
14
1
1
Order By: Relevance
“…Our data suggest that OsHT is a histidine transporter from rice. Throughout the literature, only a few members of this AAT family from higher plants have been characterized functionally (Hsu et al 1993;Fischer et al 1995;Chang and Bush 1997;Chen and Bush 1997;Fischer et al 1998;Neelam et al 1999;Okumoto et al 2002;Wipf et al 2002) and most have been obtained from the model system of A. thaliana. We believe that isolation and characterization of more transporter genes from different plant species may help us understand the mechanisms of amino acid accumulation, as well as nitrogen metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data suggest that OsHT is a histidine transporter from rice. Throughout the literature, only a few members of this AAT family from higher plants have been characterized functionally (Hsu et al 1993;Fischer et al 1995;Chang and Bush 1997;Chen and Bush 1997;Fischer et al 1998;Neelam et al 1999;Okumoto et al 2002;Wipf et al 2002) and most have been obtained from the model system of A. thaliana. We believe that isolation and characterization of more transporter genes from different plant species may help us understand the mechanisms of amino acid accumulation, as well as nitrogen metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The photoautotrophic higher plants are composed of many different enzymatic systems that carry out essential processes required for plant growth and development (Neelam et al 1999). Amino acid transport is one such fundamental process essential for resource allocation in higher plants.…”
mentioning
confidence: 99%
“…Moreover, a wide array of amino acid transporters has been identified in several different plants species, thereby providing the actual mechanisms behind amino acid uptake (e.g. Frommer et al 1993;Montamat et al 1999;Neelam et al 1999;Zhou et al 1999). The actual importance of amino acids and other sources of organic N for plant nutrition in the field is however under debate, since plants are generally considered to be inferior competitors for organic nitrogen Hodge et al 2000;Owen and Jones 2001).…”
Section: Introductionmentioning
confidence: 98%
“…Earlier studies of nutrient absorption demonstrated that higher plants could take up amino acids (Virtanen and Linkola, 1946). More recent studies of amino acid absorption have further focused on the characteristics of the carrier systems and other mechanistic aspects of the uptake process and a wide array of amino acid transporters has been identified in several different plants species (Frommer et al, 1993;Montamat et al, 1999;Neelam et al, 1999).…”
Section: Availability Of Amino Acidsmentioning
confidence: 99%